2020
DOI: 10.1016/j.chaos.2020.110173
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for COVID-19 transmission dynamics with a case study of India

Abstract: Highlights We propose a SAIU compartmental mathematical model that explains the transmission dynamics of COVID-19. Perform local and global stability analysis for the infection free and endemic equilibrium point. A sensitivity analysis is conducted to identify the most effective parameters with respect to basic reproduction number R 0 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
148
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(196 citation statements)
references
References 29 publications
3
148
0
Order By: Relevance
“…We estimated that the mean R 0 for the COVID-19 ranges from 1.58 to 2.24 ( Table 2 ) and is significantly larger than 1 and is consistent with the other estimations for the human-to-human (direct) transmission ranged from 1.3 to 7.7 ( Campos et al, 2020 ; Dropkin, 2020 ; Samui et al, 2020 ; Temime et al, 2020 ; Wei et al, 2020 ; WHO, 2020b ; Yuan et al, 2020 ; Zhang et al, 2020 ). On the other hand, most of the early predictions of mean R 0 in the literature range from 2 to 5, and are largely inconsistent with our results ( Zhao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…We estimated that the mean R 0 for the COVID-19 ranges from 1.58 to 2.24 ( Table 2 ) and is significantly larger than 1 and is consistent with the other estimations for the human-to-human (direct) transmission ranged from 1.3 to 7.7 ( Campos et al, 2020 ; Dropkin, 2020 ; Samui et al, 2020 ; Temime et al, 2020 ; Wei et al, 2020 ; WHO, 2020b ; Yuan et al, 2020 ; Zhang et al, 2020 ). On the other hand, most of the early predictions of mean R 0 in the literature range from 2 to 5, and are largely inconsistent with our results ( Zhao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…However, we have not found any article that focuses specifically on nurses' mental health during the COVID-19 outbreak. Samui et al's (19) findings suggested that COVID-19 would persist for a long time. We sought to describe the mental health of nurses in China during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…The 2019 outbreak of the new coronavirus disease (COVID- 19) in China is an epidemic threat and major public health issue (1). The World Health Organization (WHO) declared this outbreak a public health emergency of international concern on January 30, 2020 (2).…”
Section: Introductionmentioning
confidence: 99%
“…The conditions were; for R 0 < 1, the disease would stop spreading, for R 0 = 1, an infected person could infect a single person on an average and if R 0 > 1, the disease could become an epidemic (Khajanchi et al 2020a , b ). The local and global asymptotic stability analysis stated that the disease turned out to be an epidemic within a very short time and predicted that by the intervention methods of practicing social distancing, lockdown effect and use of precautionary measures like isolation, quarantine and hospitalization (Biswas et al 2020 ; Samui et al 2020 ) the transmission of the disease could be curbed. Sarkar et al ( 2020 ) concluded that the number of infected individuals might increase in India if human-to-human transmission and personal preventive measures were not applied, considering the existing rates of the testing which were lower than the required.…”
Section: Introductionmentioning
confidence: 99%